Leaders’ Power and Downward Influence Tactics: The Impact of Power Congruence - Lo, May Chiun (Life Science Journal, 2014)
Congruency has been a central concept in certain fields such as job design work values, organizational goal, and many others. There are a few factors that suggest that agreement between supervisors’ and subordinates’ are critical determinants of the liking and exchange processes. This research incorporates a basic distinction between the agent and target. Three hundred and eighty-five pairs of Malaysian managers and executives voluntarily participated in this study. The findings suggested that when both supervisors and subordinates were perceived to have position power, the use of hard influence tactics was most apparent and vice versa. Implications of the findings, potential limitations of the study, and directions for future research were discussed further.